1989
DOI: 10.1002/macp.1989.021900421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dilution during network formation on the sol fraction and elasticity of polyurethane networks

Abstract: The effect of dilution at network formation (polymer volume fraction do) = 1 -0,4) on the fraction and equilibrium photoelastic behaviour of polyurethane networks was investigated. The networks were prepared from poly(oxypropy1ene)triol and 4,4'-methylenedi(phenyl isocyanate) with various mole ratios of reactive groups 1 < rH = [OH]/[NCO] < I ,5. From a comparison between the experiments and the theory of branching processes we find that: a) with both increasing ratio rH and increasing dilution the fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…Topological defects such as loops and pendant chains are a source of decrease in the elastic modulus and the mechanical strength of the material. [10][11][12][13][14][15] Figure 5a and 5b compare the stress-strain dependencies for several films of TPGDA/E7 and GPTA/E7, respectively. The data in these figures are taken at room temperature (20 8C) on samples obtained from the relatively high EB dose of 105 kGy.…”
Section: Resultsmentioning
confidence: 99%
“…Topological defects such as loops and pendant chains are a source of decrease in the elastic modulus and the mechanical strength of the material. [10][11][12][13][14][15] Figure 5a and 5b compare the stress-strain dependencies for several films of TPGDA/E7 and GPTA/E7, respectively. The data in these figures are taken at room temperature (20 8C) on samples obtained from the relatively high EB dose of 105 kGy.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the chain ends and trapped entanglements affect the value of equilibrium modulus, 1-3 whereas the shape of viscoelastic functions in dependence on frequency and temperature in the main transition region also depends on the length of the DCs. [4][5][6][7] The strong increase in the width of the retardation spectrum with increasing number and length of dangling chains was observed for polyurethane 5,6 as well as epoxide 7 networks. It was also established that the decisive influence on the spectrum width is exerted by the increasing molecular weight of DCs.…”
Section: Introductionmentioning
confidence: 95%
“…Polymer gels have attracted considerable attention from the point of view of various physical and chemical properties 1–5. For example, hydroelectrolyte gels show a dramatic change in volume in response to change in solvent composition, pH, ionic strength, and temperature.…”
Section: Introductionmentioning
confidence: 99%